A systematic review of daily life studies on non-suicidal self-injury based on the four-function model - Hepp, Johanna; Carpenter, Ryan W.; Störkel, Lisa M.; Schmitz, Sara Elena; Schmahl, Christian; Niedtfeld, Inga (Clinical psychology review, 2020)
Non-suicidal self-injury (NSSI) is a prevalent, impairing, and trans-diagnostic behavior that can be comprehensively assessed in daily life studies. We conducted a systematic literature review of 35 Ambulatory Assessment and Daily Diary studies of NSSI, to achieve three aims. First, we reviewed descriptive evidence on NSSI acts. On average, studies observed 1.6 acts per participant, but evidence regarding methods, pain, and context was sparse. Second, we reviewed evidence on NSSI urges. On average, studies reported 4.3 urges per participant. Urges were also associated with increased negative affect and predicted later acts. Third, we reviewed evidence on the Four-function Model of NSSI. Eight studies partially supported negative intrapersonal reinforcement, showing increased negative affect pre NSSI, but, of these, only four studies supported decreased negative affect post NSSI. Additionally, only three studies supported positive intrapersonal reinforcement, showing decreased positive affect pre and increased positive affect post NSSI. Evidence for the interpersonal functions was limited to two studies and inconclusive. We recommend assessing the intensity, frequency, and context of acts and urges, as well as pain and urge duration in future studies. We also recommend follow-up prompts after acts and urges to better track affect trajectories, and a detailed assessment of interpersonal events.